Analysis Of The Possibility of Financial Statement Fraud: S.C.C.O.R.E Model - Sendifisda Faturochmah; Surya Raharja (Dinasti Publisher, 2025)
Financial statement fraud is an intentional act involving the omission of material information in financial statements. This action not only harms parties relying on financial statements but also benefits the perpetrators of the fraud. This study aims to examine the determinants of financial statement fraud using the S.C.C.O.R.E model approach. A total of 396 samples of manufacturing companies' financial statements from the 2021–2023 period were analyzed using logistic regression. The results reveal that financial stability (stimulus element), changes in directors (capability element), and total accruals (rationalization element) have a positive and significant influence on financial statement fraud. Meanwhile, other proxies such as related party transactions (collusion element), oversight effectiveness (opportunity element), and CEO photo frequency (arrogance element) do not affect financial statement fraud. This study provides practical contributions for practitioners, investors, regulators, and stakeholders in identifying the causes of fraud, thereby helping to design more effective fraud detection and prevention strategies in the future.